Analisis Lirik Lagu Slank "Gosip Jalanan" Pada Kasus Politik di Indonesia - Lintang Indra Lestari; Kun Budianto; Eraskaita Ginting (Jurnal Prodi Ilmu Politik, 2022)
This research is entitled Analysis of Slank Song Lyrics "Gosip Jalanan" in Political Cases in Indonesia. With the formulation of the problem, what is the form of criticism of political institutions in Indonesia in the lyrics of the Slank song "Gosip Jalanan" and what is the meaning of the lyrics of the Slank song "Gosip Jalanan" in political cases in Indonesia. Slank in the lyrics of his song "Gosip Jalanan" in which there are criticisms of unscrupulous political institutions with satire through the song. This study uses a qualitative method with descriptive research in the form of descriptive words, sentences, and the results of the analysis are not in the form of numbers or coefficients about the relationship between variables. In a sense, the data obtained from collecting data through the lyrics of the Slank song "Gosip Jalanan", news, videos, and the internet. The theory used in this research is the theory of political communication from Harold Lasswell. The results of this study indicate that the lyrics of the Slank song "Gosip Jalanan" contain elements of satire to the government and political institutions. And there is also a meaning in the lyrics of the Slank song "Gosip Jalanan" which is related to the attitude of the government and political institutions. Keywords: Slank song lyrics, Gosip jalanan, Political Cases.